An Innovative Interdisciplinary Teaching and Learning Methodology for Outcome Based Education - Rajendra Prasasd, M. (Journal of Engineering Education Transformations, 2017)
The Outcome-Based Education (OBE) is a scholastic method that emphasizes on what students can learn after the completion of their course or programme. Today exploring different ideas and innovation of new techniques at inter-disciplinary areas are mandatory for a fresh engineering graduate. OBE is an active learning- teaching methodology providing solution for the above problem. The courses relating to different disciplines are integrated together to implement different innovative ideas in the area of engineering education. An Innovative Interdisciplinary Teaching and Learn ing Methodology (IDTLM) is essential in the area of Electronics and Computer Engineering Education at under graduate level or any other engineering area. This paper describes about the procedure to develop IDTLM and is successfully implemented for interdisciplinary courses like Operating System and Embedded System courses for engineering graduates at Vidya Jyothi Institute of Technology, Hyderabad. This paper presents the process of implementation of IDTLM for different engineering courses and how it is useful to develop course/open-ended/academic/in house/ mini/major projects in the area of Electronics and Communication Engineering Education. This paper also explores the effective usage of IDTLM with the case study results and is compared with benefits over the Conventional Methodology (CM). The result shows the better attainment values for Course Outcomes (COS) and Program Outcomes (POS) achieved using IDTLM i n OBE implementation.